Nuclear modification factor of light neutral-meson spectra up to high transverse momentum in p-Pb collisions at √sNN=8.16 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Kroesen, Martin; et al. (Physics letters, 2022)
Neutral pion (π0) and η meson production cross sections were measured up to unprecedentedly high transverse momenta (pT) in p-Pb collisions at sNN=8.16TeV. The mesons were reconstructed via their two-photon decay channel in the rapidity interval −1.3<y<0.3 in the ranges of 0.4<pT<200 GeV/c and 1.0<pT<50 GeV/c, respectively. The respective nuclear modification factor (RpPb) is presented for pT up to of 200 and 30 GeV/c, where the former was achieved by extending the π0 measurement in pp collisions at s=8TeV using the merged cluster technique. The values of RpPb are below unity for pT<10 GeV/c, while they are consistent with unity for pT>10 GeV/c, leaving essentially no room for final state energy loss. The new data provide strong constraints for nuclear parton distribution and fragmentation functions over a broad kinematic range and are compared to model predictions as well as previous results at sNN=5.02TeV.
*ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, A. Berdnikova, L. Bergmann, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, M.K. Köhler, M. Kroesen, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, M.A. Völkl, B. Windelband [und 992 weitere Personen]
Gesehen am 16.02.2023
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol